Attachment Type Studying Of An Athletes Involved In Dancesport - Elena Spesyvykh; Valentina Voronova (Kazimierz Wielki University, 2017)
Knowledge of the individual characteristics of an athlete - this is the way to achieve high results as the sport makes certain demands to the structure of the person, of an athlete. One of the problems in the sphere of elite sport is studying and science-based education of the high-class individual athlete. The aim of the research work is studying attachment type of different qualification athletes who involved in dancesport. The studying was held in Kiev on the basis of dancesport club of the National University of Physical Education and Sports of Ukraine «Supadance», took part 84 dancers of different qualification (age 18-35 years), who were divided into 2 groups in order to identify individual characteristics and determine their impact on the successful activity in dancing: 1).highly-qualified - 44 athletes (6 - honored masters of sport; 12 - masters of international sport class; 26 - masters of sport of Ukraine; 2).qualified - 40 athletes of I category. Was used methodic of determining type of attachment by S. Hazan and F. Shaver  intended to identify the main attachment types of person in relation to another object that reflects his tendency to characteristic behavior in interpersonal relationships. Installed attachment types of athletes: stable, closed and anxious-ambivalent. According to foreign researchers, this figure is crucial for interpersonal relationships. We felt it important to study this phenomenon in relation to the «pair» kind of sport because these data can be informative for predicting the stability of the couple. Make sure to note that both groups of dancers peculiar stable attachment type, which facilitates continued cooperation; it acquires its importance for the selection to study dancesport, and at the stage of formation of couple. Prospects for further research will be studying the attachment type of dancers and their combinations in pairs at the stage of basic training.